Grain size distribution and characteristics of the tephra from the Vatnaöldur AD 871±2 and Katla 1918 eruptions, Iceland - Tinna Jónsdóttir 1983- (2015)
Detailed grain size analyses and information on particle shape characteristics of large basaltic explosive eruptions are scarce and need more attention, especially when the threat to passenger jet aircraft from ash in the atmosphere is considered. This study presents grain size distribution and shape characteristics of two large, basaltic explosive eruptions in Iceland: the AD 871±2 Vatnaöldur and the AD 1918 Katla eruptions. A total of 41 samples were collected of the AD 871±2 Vatnaöldur tephra (1.5 to 100 km from vents) and 16 samples of the AD 1918 Katla tephra (10 to 100 km from vent). This includes samples from the ablation areas of the outlet glaciers Sólheimajökull and Kötlujökull. Moreover, 3 samples from an unknown layer found in the ice below the Katla 1918 tephra in Sólheimajökull were also analyzed. Both layers are characterized by the scarcity of >1 mm particles and generally small grain size. The results also reveal a relatively small proportion of the size fraction <63 μm in all samples for the Vatnaöldur eruption ranging from 0.06 to 14.05 % of total weight percentage and a considerable loss of fines <63 μm in the surface samples collected for Katla 1918 compared with the samples collected directly from the ice. For Vatnaöldur and Katla and the unknown layer in Sólheimajökull, the grain size distributions are typical for phreatomagmatic eruptions. Scanning Electron Microscope (SEM) investigations on the grain size 3.5 ϕ shows that for both eruptions most of the tephra was fragmented in the brittle mode, blocky and angular grains are dominant in the proximal sections while slightly more vesicular grains where observed in the distal samples. More vesicular grains were present in the Katla tephra and indicate that the tephra was not fully degassed when reaching the surface. The lack of fines observed for the Vatnaöldur eruption raises questions about preservation of the tephra layer that needs to be further studied. For Katla 1918 the lack of fines in the surface samples on the outlet ...